COVID vaccine evaluation of barriers and resources among families of children with diagnosed allergies - Gooding, Gregory D.; Protudjer, Jennifer L.; Gabrielli, Sofianne; Mulé, Pasquale; Shand, Greg; Zhang, Xun; McCusker, Christine; Noya, Francisco J.; Harvey, Maria; Chalifour, Mélodie; Sicard, Catherine; Abrams, Elissa; et al. (Frontiers in Allergy, 2023)
Background We aimed to determine vaccine hesitancy and the main barriers associated with the 2019 novel coronavirus, SARS-CoV-2 (COVID-19) vaccination among families of children diagnosed with food/drug/environmental allergies. Methods Between May and June 2021, we approached 146 families seen at the outpatient allergy clinic at the Montreal Children's Hospital and a community allergy practice were invited to complete an anonymous online survey on COVID-19 and vaccination attitudes and behaviour. Uni and multivariable logistic regressions were compared to estimate factors associated with vaccine hesitancy. Results Among all patients, 24.1% reported vaccine hesitancy. The large majority of parents (95.2%) believed that vaccines work. The most common barrier to vaccination was fear of adverse side effects (57.0%). One-third of participants (31.5%) reported that a history of food, venom and drug allergy was a contraindication for COVID-19 vaccination. Fifty-nine (60.8%) participants stated that the dissemination of additional information would increase their willingness to be vaccinated. Most (96.9%) parents reported that their children's vaccinations were up to date. Hesitant families were more likely to be parents of children aged 6–10 years, be of Asian descent, report that mRNA vaccines are riskier than traditional vaccines, and report that the vaccine should not be given if the child has a history of allergic reaction to vaccines. Conclusion Vaccine hesitancy exists mainly among certain ethnic groups and families with young children. Allergies to food, venom and drug allergy are commonly perceived as contraindications for COVID-19 vaccination. Knowledge translation activities addressing parental concerns will help increase vaccination rates.